Erzähler des Allwissenden: Überlegungen zur Sprachform der Glaubwürdigkeit des Glaubens - Bründl, Jürgen (Zeitschrift für katholische Theologie, 2010)
Faith is characterized by an unsolvable problem of justification. While St. Paul concludes the truth of the faith from the practice (cf. 1. Thess 2,13), the Evangelists quote Jesus Christ as important witness (cf. Mk 1,1–3), who bears witness to himself in a decisive moment (cf. Joh 8,12–20). Who legitimates the omniscient narrator of these christological confessions? By means of Genette's narrative theory and the hermeneutic theories of Bultmann and Fuchs, the specific demand which faith puts onto the human being, becomes apparent: the auctorial narrative form frees the fundamental narrations of faith from any kind of human justification, thus marking the special credibility which is inherent to listening to God's words.